Manifestation of prosocial and antisocial behaviour in a youth basketball match - Sukys, S.; Mankute, G. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Examining behavior in a youth girls basketball match it was hypothesized that players and coaches` behaviors would differ in relation with players` age, course and the final outcome of the match. Research aim was to explore the manifestation of observed prosocial and antisocial behaviors in a youth girls basketball match. Research methods. Fourty games were observed: 20 matches by U15 and 20 matches by U17 age groups. Research results. Younger players more often argued with the referees (p = 0.03), used physical aggression (p = 0.04). In the second half of the game players more often quarreled with referees (p = 0.05), welcomed unsuccessful actions of the rivals (p = 0.03). When the difference in the final result of the game was low, players more argued with the referees (p = 0.001) and used physical aggression (p = 0.01). Coaches working with younger players showed disrespect to them more often (p = 0.001). Such behaviours were more often at the beginning of the game (p = 0.001) and when the difference in the final result of the game was low (p = 0.04). Discussion and conclusions. Research did not confirm that younger basketball players more often demonstrated respect to referee`s decisions and opponents. Research confirmed that antisocial behaviors of players were more common in the second half of the match and when the difference in the final result was less. Research confirmed that coaches who worked with younger players demonstrated more antisocial behavior and that such behavior was more common when there was less difference in the results of the match.